Increased apoptotic cell death in the neointima after stent-based vascular irradiation: role of radiation-induced apoptosis for restenosis reduction - Hehrlein, Christoph; Kollum, Marc; Arab, Amina; Kamencic, Huse; Metz, Jürgen (Journal of interventional cardiology, 1999)
Background: Restenosis after stent implantation is a common problem faced today by interventional cardiologists. It is primarily caused by excessive neointimal growth. Early clinical studies showed substantial reductions of neointimal volumes within bodies of32P radioactive coronary stents. Radiotherapy induces programmed cell death (apoptosis) in tumors but there is still debate whether irradiation causes apoptosis in arteries. Methods: We compared the time course of neointimal apoptosis after implanting 7-mm long 32P radioactive slotted tubular stents in rabbit iliac arteries. The stents were homogeneously ion-implanted with 32P at activity levels of 0.5 and 6 μCi. These stents produce continuous beta-particle emission at very low dose rates. Neointima formation was compared with nonradioactive stents by histomorphometry after 1, 4, and 12 weeks. Apoptosis was detected using the terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL) assay method and transmission electron microscopy. Results: At an early follow-up of 1 week after stent implantation, no changes in neointimal apoptosis were found. The 32P stents at activities of 6 μCi, but not of 0.5 μCi, reduced neointimal crosssectional areas and cell numbers compared with control stents after 4 and 12 weeks. Apoptosis in the neointima increased after 4 weeks and was substantially elevated 12 weeks after implantation of 6 μCi 32P stents compared with 0.5 μCi and control stents (16% vs 6% and 3%, P < 0.01 for 6 vs 0.5 μCi and control stents, respectively). Conclusions: In this study, a dose dependent decrease in neointimal thickening and cell density within 32P beta-particle emitting stents was associated with an increased frequency of apoptosis. This increase in apoptosis occurred late in the time course of vascular healing after the implantation of 32P beta-particle emitting stents. Apoptosis seems to be involved in the mechanisms by which stent-based vascular irradiation reduces neointimal hyperplasia.